Liberia Poverty Note : Tracking the Dimensions of Poverty - World Bank (Washington, DC, 2013)
Poor governance and nearly fifteen years of brutal conflict have made Liberia one of the poorest countries in the world. An important objective for the democratically elected government of post-conflict Liberia is to reduce poverty. As part of its long-term vision plan, the Government is preparing a second Poverty Reduction Strategy (PRS) to set out its medium-term approach to poverty reduction. The current climate of peace and security, as well as continued improvements in the economy, offer the Government a unique opportunity to improve on the gains that it has made in reducing poverty under its previous PRS. However, as cross-country evidence has shown, growth alone is not sufficient for poverty reduction. The Government must also take steps to break the cycle of chronic poverty by ensuring that the poor are given opportunities and support to emerge from poverty, and that those who have emerged from poverty do not fall back into poverty. This poverty note is intended to assist the Government in formulating evidence based policies aimed at poverty reduction. This policy note draws from rich information provided by the 2007 and 2010 Core Welfare Indicator Questionnaires (CWIQs). It also benefits from qualitative data from a relatively large number of focus groups on gender and youth. In addition, the note benefits from the analysis contained in the 2011 human opportunities report for Liberia, which focuses in particular on access to education.